Applying genome-wide CRISPR to identify known and novel genes and pathways that modulate formaldehyde toxicity. (April 2021) - Zhao, Yun; Wei, Linqing; Tagmount, Abderrahmane; Loguinov, Alex; Sobh, Amin; Hubbard, Alan; McHale, Cliona M.; Chang, Christopher J.; Vulpe, Chris D.; Zhang, Luoping
Abstract: Formaldehyde (FA), a ubiquitous environmental pollutant, is classified as a Group I human carcinogen by the International Agency for Research on Cancer. Previously, we reported that FA induced hematotoxicity and chromosomal aneuploidy in exposed workers and toxicity in bone marrow and hematopoietic stem cells of experimental animals. Using functional toxicogenomic profiling in yeast, we identified genes and cellular processes modulating eukaryotic FA cytotoxicity. Although we validated some of these findings in yeast, many specific genes, pathways and mechanisms of action of FA in human cells are not known. In the current study, we applied genome-wide, loss-of-function CRISPR screening to identify modulators of FA toxicity in the human hematopoietic K562 cell line. We assessed the cellular genetic determinants of susceptibility and resistance to FA at 40, 100 and 150 μM (IC10, IC20 and IC60, respectively) at two time points, day 8 and day 20. We identified multiple candidate genes that increase sensitivity (e.g. ADH5, ESD and FANC family) or resistance (e.g. FASN and KDM6A ) to FA when disrupted. Pathway analysis revealed a major role for the FA metabolism and Fanconi anemia pathway in FA tolerance, consistent with findings from previous studies. Additional network analyses revealed potential new roles for one-carbon metabolism, fatty acid synthesis and mTOR signaling in modulating FA toxicity. Validation of these novel findings will further enhance our understanding of FA toxicity in human cells. Our findings support the utility of CRISPR-based functional genomics screening of environmental chemicals. Graphical abstract: Image 1 Highlights: Multiple genes related to FA cellular toxicity were identified using genome-wide CRISPR. FA metabolism and the Fanconi anemia pathway were confirmed to modulate FA tolerance. New genes in one-carbon metabolism were found to be associated with FA toxicity. Novel pathways including fatty acid synthesis and mTOR signaling were discovered to modulate FA toxicity.